Pengaruh Good Corporate Governance, Metode Pembayaran dan Kepercayaan terhadap Keputusan Muzakki dalam Membayar Zakat di BAZNAS Kabupaten Batang Hari - Delvia Indah Azhari; Habriyanto Habriyanto (Lembaga Yasin AlSys, 2026)
The management of zakat through official institutions is a strategic instrument for improving societal welfare; however, studies that specifically examine the influence of good corporate governance, payment methods, and trust on muzakki decisions at the regency level remain limited. This study aimed to analyze the influence of good corporate governance, payment methods, and trust on muzakki decisions in paying zakat at the Badan Amil Zakat Nasional (BAZNAS) of Batang Hari Regency. A quantitative approach with an explanatory survey design was employed, involving 93 muzakki selected using probability sampling based on Slovin’s formula. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression preceded by validity, reliability, and classical assumption tests. The results showed that good corporate governance, payment methods, and trust had a positive and significant effect on muzakki decisions, both partially and simultaneously. These findings deepen the understanding of the roles of sound institutional governance, the availability of convenient and varied payment methods, and institutional trust in shaping zakat payment behavior. The study concludes by emphasizing the importance of strengthening management transparency, innovating payment systems, and implementing public trust-building strategies to increase muzakki participation, while also providing a theoretical contribution to zakat management studies and practical recommendations for zakat institutions in enhancing the effectiveness of fund collection.